Overview of Chest Radiology Images of Coron avirus Disease 2019 (COVID-19) Patients at Undata General Hospital, Palu, Indonesia - Nurahalisa, Siti; Sulistiana, Ria (Sriwijaya Journal of Radiology and Imaging Research, 2023)
Introduction: M aking a diagnosis of COVID-19 requires quite sophisticated technology and tools. To make a diagnosis of COVID-19, a technology and tool are needed that can identify the presence of the genetic material of the SARS-CoV-2 virus. How ever, the existence of PCR tools cannot be spread evenly in various regions of Indonesia because the tools are quite difficult to operate and require adequate laboratory facilities. The radiological image of the chest is a promising supporting examination to be developed as a supporting examination to diagnose COVID-19. This study aimed to obtain an overview of chest radiology image s of COVID-19 patients at Undata General Hospital, Palu, Indonesia. Methods: This study is a descriptive observational study. A total of 20 research su bjects participated in this study. Observations of chest radiological images are presented in a univariate manner in the form of the frequency distribution of data using SPSS software. Results: Study subjects with mild degree s of COVID-19 had normal chest X-rays. Meanwhile, research subjects with moderate degrees of COVID-19 generally have a chest X-ray photo in the form of an infiltrate. Study subjects with severe COVID-19 had a chest X-ray image in the form of consolidated-ground glass opacity. Conclusion: The more severe the degree of COVID-19 is in line with the higher the inflammation in the lung tissu e, so a radiological image of the thorax appears in the form of a consolidated-ground glass opacity image.